2023
DOI: 10.1371/journal.pone.0293603
|View full text |Cite
|
Sign up to set email alerts
|

Associations between personal apparent temperature exposures and asthma symptoms in children with asthma

Linchen He,
Shoshana Evans,
Christina Norris
et al.

Abstract: Ambient temperature and relative humidity can affect asthma symptoms. Apparent temperature is a measure of temperature perceived by humans that takes into account the effect of humidity. However, the potential link between personal exposures to apparent temperature and asthma symptoms has not been investigated. We conducted a panel study of 37 asthmatic children, aged 5–11 years, during an early spring season (average daily ambient temperature: 14°C, range: 7–18°C). Asthma symptoms were measured 4 times for ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The AT has been observed to more objectively reflect human thermal perception compared to the mere ambient temperature in the European study [ 52 ]. He et al found AT exposure were more effective than ambient temperature in influencing variability of asthma symptoms [ 53 ]. However, the effectiveness of ambient temperature and AT of the perception of cold stress was not well established.…”
Section: Discussionmentioning
confidence: 99%
“…The AT has been observed to more objectively reflect human thermal perception compared to the mere ambient temperature in the European study [ 52 ]. He et al found AT exposure were more effective than ambient temperature in influencing variability of asthma symptoms [ 53 ]. However, the effectiveness of ambient temperature and AT of the perception of cold stress was not well established.…”
Section: Discussionmentioning
confidence: 99%